Developing Learn English Better (LEB) For Grammatical Skills - Mohammad Ashari Ridho; Yuyun Bahtiar; Akhmad Kanzul Fikri (APPLICATION: Applied science in Learning Research, 2022)
The purpose of this research is to improve student's English skills in grammar skills through android-based learning media. This research uses R&D research method. The data collection in this study was obtained by sharing questioner, to know the needs and obstacles experienced by students in learning grammar. To meet validity and reliability, the researchers used two validators tasked with testing the feasibility of learning media for students to use. Testers consist of material experts and media design experts. The results of this study show that application-based learning media is feasible to use. Improvements can be seen from the use of data analysis techniques to calculate scores from questionnaires using Linkert scale techniques with 5 answer options. According to the assessment by 15 students, the total score obtained was 593, the total score was then calculated using the formula described earlier to determine the feasibility of learning media. The average score obtained from the respondence is 39.5, the data then re-calculates. So, the assessment results by respondents were 3.95 which fall into the category of good and worth using. The benefits of research conducted to facilitate students in learning grammar using android applications. Based on the results of the study, students can conclude that learning grammar is easier using the Grammar Android Application.